2016
DOI: 10.1111/idh.12229
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating the efficacy of a 67% sodium bicarbonate toothpaste on gingivitis

Abstract: A randomized controlled trial evaluating the efficacy of a 67% sodium bicarbonate toothpaste on gingivitis Abstract: Introduction: In previous studies, toothpastes with high levels of sodium bicarbonate (>50%) have reduced gingival inflammation and oral malodour. This study compared the effects of brushing for 6 weeks with 67% (test group) or 0% (control group) sodium bicarbonate toothpaste on gingival health. Methods: This was a single-centre, single examiner-blind, randomized, controlled, twotreatment, paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The search of the MEDLINE‐PubMed and Cochrane‐CENTRAL databases resulted in 184 unique papers. Manual searching of the reference lists of the final selected papers provided two additional relevant papers, Al‐Kholani et al, listed by Hosadurga et al and Akwagyiram et al, listed by Bosma et al Altogether, 21 eligible publications were found . Among these, Putt et al and Mason et al provided five and two sub‐studies, respectively, within their main publications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search of the MEDLINE‐PubMed and Cochrane‐CENTRAL databases resulted in 184 unique papers. Manual searching of the reference lists of the final selected papers provided two additional relevant papers, Al‐Kholani et al, listed by Hosadurga et al and Akwagyiram et al, listed by Bosma et al Altogether, 21 eligible publications were found . Among these, Putt et al and Mason et al provided five and two sub‐studies, respectively, within their main publications.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking status was generally unclear. Hosadurga et al specifically excluded smokers, and only Lomax et al, Jose et al and Akwagyiram et al reported the smoking status of the included participants. The duration of follow‐up studies ranged from 1 month to 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are multiple clinical studies that have measured the effect of baking soda dentifrices in the control of plaque and gingival inflammation. Some studies 16,19,21,29,[39][40][41][42] have not shown baking soda to be comparatively more efficacious in reduction of plaque and gingival inflammation when compared with dentifrices that contain triclosan or herbal ingredients. Conversely, several studies have demonstrated that baking soda dentifrices are superior to control dentifrices in the control of plaque and gingivitis.…”
Section: Discussionmentioning
confidence: 99%